Chemotherapy During Active SARS-CoV2 Infection: A Case Report and Review of the Literature - Woźniak, Krzysztof; Sachs, Wojciech; Boguradzki, Piotr; Basak, Grzegorz Władysław; Stec, Rafał (Frontiers in Oncology, 2021)
COVID-19 has become the biggest public health problem and one of the most important causes of death in many countries in the world. SARS-CoV-2 infection is most likely to be fatal in elderly patients with concomitant diseases. In this article we present two cases of asymptomatic SARS-CoV-2-positive patients suffering from cancer who were treated with chemotherapy. The first case, a patient with primary mediastinal B-cell lymphoma, shows that confirmed SARS-CoV-2 infection does not have to be a contraindication to chemotherapy. We describe the course of disease and discuss doubts related to the choice of chemotherapy regimen. The second patient was a male with metastatic sigmoid cancer treated with FOLFOX4 as first-line palliative chemotherapy. This case draws attention to asymptomatic SARS-CoV-2 carriers who underwent chemotherapy. Our patient was safely treated with chemotherapy without long break caused by viral infection. It should be remembered that there are asymptomatic carriers among cancer patients and that they may spread infection to others. On the other hand, delaying chemotherapy can cause rapid disease progression and reduce overall survival of our patients.